2018
DOI: 10.3389/fcimb.2018.00126
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons Between Bacterial Communities in Mucosa in Patients With Gastric Antrum Ulcer and a Duodenal Ulcer

Abstract: Objective: To identify and compare the bacterial community profile of mucosal tissues from a gastric antrum ulcer and a duodenal ulcer in Helicobacter pylori (Hp) positive dyspeptic patients.Methods: Genomic DNA was extracted from the mucosal tissues obtained from 18 patients diagnosed with gastric antrum or duodenal ulcers. A library was constructed using 16S rRNA gene amplification, and Miseq high-throughput sequencing was used to analyse the amplified products. Bioinformatics methods, including operational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
15
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 13 publications
3
15
0
2
Order By: Relevance
“…Another study compared mucosal microbiota composition in duodenal and gastric ulcers and showed that the same genera are present in both locations, and again showed different abundance of genera including Prevotella , Neisseria and Streptococcus which were significantly lower in gastric samples when compared to duodenal samples. However, this might be a consequence of ecosystem changes due to the presence of Helicobacter . Many predominant gastric and oral bacteria such as Lactobacillus , Streptococcus or Veillonella species are very active in the small intestine .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study compared mucosal microbiota composition in duodenal and gastric ulcers and showed that the same genera are present in both locations, and again showed different abundance of genera including Prevotella , Neisseria and Streptococcus which were significantly lower in gastric samples when compared to duodenal samples. However, this might be a consequence of ecosystem changes due to the presence of Helicobacter . Many predominant gastric and oral bacteria such as Lactobacillus , Streptococcus or Veillonella species are very active in the small intestine .…”
Section: Resultsmentioning
confidence: 99%
“…However, this might be a consequence of ecosystem changes due to the presence of Helicobacter 54. Many predominant gastric and oral bacteria such as Lactobacillus, Streptococcus or Veillonella species are very active in the small intestine 55.…”
mentioning
confidence: 99%
“…The relative abundance of the phylum Bacteroidetes in the LBP and MIX groups tended to be slightly increased, but was not significantly different among five groups. The phyla Proteobacteria , Bacteroidetes , and Firmicutes were predominant in patients with Helicobacter pylori -positive gastric antrum ulcer or duodenal ulcer [ 69 ]. The phylum Proteobacteria was mostly abundant in gastric antrum of the patients with Helicobacter pylori -positive gastric antrum ulcer, and the phyla Bacteroidetes and Firmicutes were mostly abundant in the duodenum of patients with Helicobacter pylori -positive duodenal ulcers [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Prevotella, Neisseria, Staphylococcus, and Streptococcus have been reportedly found in the stomach; however, some of these bacteria were found also in the esophagus with less-studied clinical relevance. [5][6][7] Evidence suggests that colonization by some species, for example, Streptococcus salivarius, which have urease activity, generates a less acidic environment, thus favoring H. pylori colonization. 8 Hansson et al have described that the production of acid in the antrum is increased mainly after gastritis whereas the risk of gastric cancer is slightly reduced.…”
Section: Introductionmentioning
confidence: 99%